A ZTA composite ceramic with high zero stress temperature point and preparation method thereof

By coating the mixed coating of cyanite and cordierite on the surface of ZTA ceramics, the residual compressive stress is introduced, and the problem of low zero stress temperature point of ZTA ceramics is solved, which significantly improves its high-temperature service performance.

CN116715510BActive Publication Date: 2025-04-08CHINA TEST & CERTIFICATION INT GRP CO LTD +1
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202310697981.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-06-13
Publication Date
2025-04-08
Estimated Expiration
2043-06-13

AI Technical Summary

Technical Problem

The existing ZTA ceramics have low zero stress temperature points, which limits their service performance in high temperature environments.

Method used

By coating the surface of the unsintered ZTA sample with a mixture of cyanite and cordierite, after co-firing at the same temperature, residual compressive stress is introduced on the surface of ZTA ceramics by using the difference in the expansion coefficients of the coating and the substrate to optimize the ratio of cyanite and cordierite and increase the zero-stress temperature point.

Benefits of technology

It significantly improves the zero-stress temperature point of ZTA composite ceramics, improves its strength and toughness in high-temperature environments, and extends the high-temperature service performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116715510B_ABST
    Figure CN116715510B_ABST
Patent Text Reader

Abstract

The present invention discloses a ZTA composite ceramic with a high zero stress temperature point and a preparation method thereof, and belongs to the technical field of ceramic-based composite material preparation. The present invention adopts a mixed powder of kyanite and cordierite in a specific ratio as a coating, and a ZTA ceramic as a matrix, and a coating of a certain thickness is coated on the ZTA embryo by a "coating method", and after co-firing at the same temperature, a ZTA composite ceramic with a higher zero stress temperature point is obtained. The ZTA composite ceramic prepared by the present invention has the advantages of excellent mechanical properties at room temperature, good high temperature performance, and a wider high temperature working range. The preparation method of the present invention is simple, low-cost, and has obvious reinforcement effect. It has good high-temperature service performance and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of preparation of ceramic-based composite materials, in particular to a ZTA composite ceramic with a high zero stress temperature point and a preparation method thereof. Background Art

[0002] ZTA is zirconia toughened alumina ceramics, which has excellent properties such as high temperature resistance, high strength, high hardness, and good insulation. It is an ideal structural ceramic material and is widely used in aviation, aerospace, shipbuilding, weapons, electronics, nuclear industry and other fields. However, with the continuous application of ZTA in some high-temperature fields, higher requirements are put forward for its high-temperature resistance.

[0003] In order to improve the service safety and reliability of ZTA ceramics, the commonly used strengthening and toughening methods are: (1) introduction of reinforcement phases such as particles, fibers, and whiskers; (2) phase transformation toughening; (3) optimization of sintering process; (4) prestressing strengthening. Among them, prestressing strengthening is the simplest and most economical method, which is suitable for improving the performance of brittle materials.

[0004] For prestressed ceramics, the zero stress temperature point, that is, the temperature point at which the prestress completely disappears, plays a decisive role in the high-temperature service performance of the material. Therefore, in order to improve the high-temperature service performance of ZTA ceramics, it is necessary to increase its zero stress temperature point.

[0005] Patents CN110028314B, CN1785909A and CN103664153B indicate that cordierite-mullite system is widely used in refractory products such as kiln furniture and kilns due to its advantages of low expansion coefficient, high strength, good thermal shock resistance and oxidation resistance. However, no further research has been conducted on the high temperature resistance of the prepared composite ceramics. Summary of the invention

[0006] In order to improve the high temperature resistance of ZTA ceramics, the present invention provides a ZTA composite ceramic with a high zero stress temperature point and a preparation method thereof. The present invention introduces residual compressive stress on the surface of the ZTA ceramic by coating a coating of a mixture of kyanite and cordierite on the surface of an unsintered ZTA sample, and after co-firing at the same temperature, utilizing the difference in expansion coefficient between the coating and the substrate. By optimizing the ratio of kyanite to cordierite, a ZTA composite ceramic with a higher zero stress temperature point is obtained.

[0007] In order to solve the above technical problems, the present invention provides the following technical solutions:

[0008] On the one hand, the present invention provides a high zero stress temperature point ZTA composite ceramic, wherein the prestressed ceramic uses ZTA as a matrix, and a ceramic coating with a thickness of 10-200 μm is provided on the upper and lower surfaces, and the thickness ratio of the matrix to the coating is greater than 10.

[0009] Furthermore, the coating raw material is a mixture of kyanite and cordierite, wherein the content of cordierite is 5wt%-50wt%.

[0010] Furthermore, in the ZTA matrix, the mass fraction of ZrO2 is 5-50wt%, and the rest is Al2O3 and a small amount of additives.

[0011] On the other hand, the present invention also provides a method for preparing a ZTA composite ceramic material with a high zero stress temperature point, comprising:

[0012] (1) Preparation of ZTA green body: dry pressing is adopted, and the process parameters are: pressure 50-100MPa, holding time 1-10min to obtain the formed green body; then the green body is further cold isostatically pressed at a pressure of 200-350MPa, holding time 1-10min. Finally, the green body is pre-sintered and debonded, the sintering temperature is 800-1200℃, and the temperature is kept for 0.5-1h;

[0013] (2) Preparation of coating slurry: Mix the kyanite and cordierite mixed powder, dispersant, and binder in alcohol or water, and disperse them into coating slurry by high-speed ball milling;

[0014] (3) Coating the surface of the green body: The coating slurry is evenly coated on the surface of the pre-fired ZTA green body to obtain a "sandwich" structure, and finally dried in the shade for 2-24 hours; the thickness of the coating can be determined according to the number of coatings;

[0015] (4) Sintering of ZTA composite ceramic materials: heat the temperature from room temperature to 800-1400°C at a rate of 2-10°C / min, and keep it at that temperature for 0.5-1h; then heat the temperature to 1550-1600°C at a rate of 2-20°C / min, and keep it at that temperature for 1-3 hours; then cool the temperature to 800°C at a rate of 3-5°C / min, and then cool it in the furnace.

[0016] Furthermore, the ZTA powder is mainly composed of ZrO2 and Al2O3, wherein the mass fraction of ZrO2 is 5-50wt%, and the rest is Al2O3 and a small amount of additives.

[0017] The binder is one of polyvinyl butyral or ISOBAM.

[0018] Furthermore, the dispersant is one or more of castor oil, sodium citrate, and polyacrylic acid.

[0019] Furthermore, the amount of the binder is 1 to 10% of the mass of the coating powder; the amount of the dispersant is 0.1 to 1% of the mass of the coating powder.

[0020] Furthermore, the ball milling speed is 100 to 500 rpm, and the ball milling time is more than 1 hour.

[0021] The kyanite selected in the present invention has the characteristics of low price and low expansion coefficient; when the temperature exceeds 1000°C, it begins to decompose into mullite and SiO2 phases; when the temperature exceeds 1500°C, the kyanite is completely decomposed.

[0022] Compared with the prior art, the present invention has the following beneficial effects:

[0023] The method adopted by the present invention is prestressed reinforcement. A mixed powder of kyanite and cordierite with a low expansion coefficient is selected as a coating raw material. Compressive stress is introduced into the surface of ZTA ceramics through a "coating method" to obtain a ZTA composite ceramic with a wider high-temperature working area, high strength and high toughness.

[0024] The composite ceramic of the present invention, which uses a specific ratio of kyanite and cordierite mixed powder as a coating and ZTA as a matrix, not only has good interface bonding, but also has high density. Compared with pure ZTA ceramics, kyanite coating / ZTA composite ceramics, and cordierite coating / ZTA composite ceramics prepared under the same process, its zero stress temperature point can be increased by 200°C, and has better high-temperature service performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] Figure 1 It is a schematic diagram of the structure of the ZTA composite ceramic of the present invention;

[0026] Figure 2 A scanning electron microscope of the ZTA composite ceramic prepared in Example 1 of the present invention;

[0027] Figure 3 Temperature-strength curves of the kyanite-cordierite / ZTA-30 composite ceramic prepared in Example 1 of the present invention, the pure ZTA-30 ceramic of Comparative Example 1, the cordierite / ZTA-30 composite ceramic of Comparative Example 2, and the kyanite / ZTA-30 composite ceramic of Comparative Example 3. DETAILED DESCRIPTION

[0028] In order to make the technical problems to be solved, technical solutions and advantages of the present invention more clear, a detailed description will be given below with reference to the accompanying drawings and specific embodiments.

[0029] In the present invention, the materials and reagents used are commercially available unless otherwise specified. Kyanite powder: produced by Zhengzhou Boya Refractory Materials Co., Ltd., with an average particle size of 4.21 μm. Cordierite powder: produced by Henan Borun Casting Materials Co., Ltd., with an average particle size of 4.8 μm. ZTA ceramic powder: ZTA ceramic powder is Japan Marumi JZL-Z30 granulation powder (marked as: ZTA-30), in which the mass fraction of ZrO2 is 30.3wt.%, Al2O3 is 67.3wt.%, Y2O3 is 1.7wt.%, and the balance is other components.

[0030] The present invention provides a ZTA composite ceramic with a high zero stress temperature point and a preparation method thereof, and specific embodiments are as follows.

[0031] Example 1

[0032] A method for preparing a ZTA composite ceramic with a high zero stress temperature point, comprising:

[0033] (1) Weigh 25 g of ZTA ceramic powder and use The stainless steel mold was molded at a pressure of 50MPa for 1min. The formed green body was densified by cold isostatic pressing at a pressure of 300MPa for 5min to obtain a green body. The green body was pre-sintered in a high-temperature furnace at a heating rate of 2℃ / min, sintering temperature of 1000℃, and heat preservation for 1h to obtain a ZTA green body. It was then cut to a size of 4×5×38mm, chamfered, and surface polished to obtain a ZTA green body spline.

[0034] (2) Kyanite-cordierite mixed slurry: 12 g kyanite powder, 8 g cordierite powder, 100 ml alcohol, 1.0 g Isobam powder and 2 drops of castor oil were mixed and placed in a planetary ball mill with a ball-to-material ratio of 10:1 and a rotation speed of 300 r / min for 48 h to obtain a uniform surface slurry;

[0035] (3) Using the "coating method", the slurry in step 2 is evenly coated on the surface of the ZTA embryo specimen in step 1, and the coating is repeated twice after drying in the shade to obtain three types of ZTA composite ceramics with a "sandwich structure"; the coating thickness before sintering is about 60 μm, and it is naturally dried for 12 hours to obtain a ZTA specimen with a slurry on the surface.

[0036] Step 4: The ZTA sample with slurry on the surface obtained in step 3 is subjected to pressureless sintering in a high-temperature furnace. The sintering process parameters are: heating to 1400°C at a heating rate of 2°C / min and keeping at that temperature for 1 hour; then heating to 1600°C at a heating rate of 5°C / min and keeping at that temperature for 2 hours, and finally cooling to 800°C at a cooling rate of 5°C / min and cooling with the furnace to obtain kyanite-cordierite / ZTA-30 composite ceramics. Schematic diagram of the prepared composite ceramic structure Figure 1 The cross-sectional SEM image is shown in Figure 2 , and its surface coating thickness is about 50.8μm.

[0037] To further illustrate the beneficial effects of the present invention, a comparative example is constructed as follows.

[0038] Comparative Example 1

[0039] In this comparative example, steps (2)-(3) were omitted, and the remaining conditions were the same as those in Example 1.

[0040] Comparative Example 2

[0041] In this comparative example, cordierite was replaced by an equal amount of kyanite, and the other conditions were the same as those in Example 1.

[0042] Comparative Example 3

[0043] In this comparative example, kyanite was replaced by an equal amount of cordierite, and the other conditions were the same as those in Example 1.

[0044] The three-point bending strength of the ceramic material prepared above at 800-1300°C is as follows Figure 3 As shown. At 800-1000°C, the strength of the three ZTA-30 composite ceramics is higher than that of pure ZTA-30 ceramics. The zero stress point temperature of kyanite / ZTA-30 composite ceramics and cordierite / ZTA-30 composite ceramics is about 1000°C; while the kyanite-cordierite / ZTA-30 composite ceramics prepared by the process of the present invention has a bending strength of about 113% of that of kyanite / ZTA-30 composite ceramics and cordierite / ZTA-30 composite ceramics at 1000°C, and its zero stress temperature point is 1200°C, which is increased by 20%, and has better high temperature resistance.

[0045] Example 2

[0046] A method for preparing a ZTA composite ceramic with a high zero stress temperature point, comprising:

[0047] (1) Weigh 25 g of ZTA ceramic powder and use The stainless steel mold was molded at a pressure of 60MPa for 5 minutes. The formed green body was densified by cold isostatic pressing at a pressure of 200MPa for 10 minutes to obtain a green body; the green body was pre-sintered in a high-temperature furnace at a heating rate of 2℃ / min, sintering temperature of 800℃, and heat preservation for 1h to obtain a ZTA green body. It was then cut to a size of 4×5×38mm, chamfered, and surface polished to obtain a ZTA green body spline.

[0048] (2) Kyanite-cordierite mixed slurry: 19 g kyanite powder, 1 g cordierite powder, 100 ml alcohol, 1.0 g Isobam powder and 2 drops of sodium citrate were mixed and placed in a planetary ball mill with a ball-to-material ratio of 10:1 and a rotation speed of 300 r / min for 24 h to obtain a uniform surface slurry;

[0049] (3) Using the "coating method", the slurry in step 2 is evenly coated on the surface of the ZTA embryo specimen in step 1 and dried in the shade; then the coating is repeated twice and naturally dried for 12 hours to obtain a ZTA specimen with a slurry on the surface.

[0050] Step 4: The ZTA specimen with slurry on the surface obtained in step 3 is pressurelessly sintered in a high-temperature furnace. The sintering process parameters are: heating to 1400°C at a heating rate of 5C / min, keeping warm for 1h, then heating to 1600°C at a heating rate of 5°C / min and keeping warm for 2 hours, and finally cooling to 800°C at a cooling rate of 5°C / min and cooling with the furnace to obtain kyanite-cordierite / ZTA-30 composite ceramics.

[0051] Example 3

[0052] In step (2) of this embodiment, the amount of kyanite powder used is 10 g, the amount of cordierite powder used is 10 g, and the other conditions are the same as those in embodiment 1.

[0053] Example 4

[0054] In step (2) of this embodiment, the amount of kyanite powder used is 16 g, the amount of cordierite powder used is 4 g, and the other conditions are the same as those in embodiment 1.

[0055] Example 5

[0056] Step (3) of this embodiment is specifically as follows: the slurry in step 2 is evenly coated on the surface of the ZTA embryonic body sample in step 1, and dried in the shade; then the coating is repeated 5 times, and naturally dried for 12 hours to obtain a ZTA sample with a slurry on the surface. The other conditions are the same as those in embodiment 1.

[0057] Comparative Example 4

[0058] In step (2) of this comparative example, the amount of kyanite powder used is 8 g, the amount of cordierite powder used is 12 g, and the other conditions are the same as those in Example 1.

[0059] The present invention adjusts the amount of kyanite powder and cordierite powder, and finds that when the amount of cordierite powder is 5-50wt% of the powder, the zero stress temperature point of the prepared composite ceramic is 1100-1200°C, which is better than kyanite / ZTA-30 composite ceramics and cordierite / ZTA-30 composite ceramics. When the amount of cordierite powder is adjusted to 60% of the powder, the zero stress temperature point of the prepared composite ceramic is only 1000°C.

[0060] Comparative Example 5

[0061] In this comparative example, the kyanite powder was replaced with an equal amount of mullite powder, and the other conditions were the same as those in Example 1.

[0062] The zero stress temperature of the composite ceramic obtained by replacing kyanite powder with mullite powder is 1000°C, which may be due to (1) the densification sintering temperature: the densification sintering temperature of mullite is higher than that of ZTA; (2) the SiO2 phase produced by the decomposition of kyanite can continue to react with the Al2O3 component in the ZTA matrix, thus facilitating the formation of a strong interface bond between the coating and the matrix.

[0063] In summary, the coating slurry prepared from the kyanite powder and cordierite powder in a specific ratio in the present invention can significantly increase the zero stress temperature point of the composite ceramic after coating, so that it has better high-temperature service performance.

[0064] The above is a preferred embodiment of the present invention. For ordinary technicians in this technical field, making several improvements and modifications without departing from the principles of the present invention should also be regarded as within the protection scope of the present invention.

Claims

1. A method for preparing a ZTA composite ceramic with a high zero stress temperature point, characterized in that: include: (1) Preparation of ZTA green body: ZTA powder is dry pressed at a pressure of 50-100 MPa for 1-10 min, then cold isostatically pressed at a pressure of 200-350 MPa for 1-10 min, and finally heated at 800-1200°C for 0.5-1 h to obtain green body; (2) Preparation of coating slurry: Mix coating powder, dispersant and binder in alcohol or water, and ball mill to make the coating slurry evenly dispersed; the coating powder is a mixed powder of kyanite and cordierite, wherein the content of cordierite is 5-50wt% of the mass of the coating powder; the binder is polyvinyl butyral ester or ISOBAM; the dispersant is one or more of castor oil, sodium citrate and polyacrylic acid; the amount of the binder is 1-10% of the mass of the coating powder; the amount of the dispersant is 0.1-1% of the mass of the coating powder; (3) coating the green body: coating the upper and lower surfaces of the green body prepared in step (1) with the coating slurry respectively, and drying in the shade; then repeating the coating and shade drying process until the coating reaches a certain thickness; (4) Sintering of composite ceramics: Heat the temperature from room temperature to 800-1400°C at a heating rate of 2-10°C / min and keep it at that temperature for 0.5-1h; then heat the temperature to 1550-1600°C at a heating rate of 2-20°C / min and keep it at that temperature for 1-3h, then cool the temperature to 800°C at a heating rate of 3-5°C / min and finally cool it in the furnace to obtain ZTA composite ceramics.

2. The preparation method according to claim 1, characterized in that: The ball milling speed is 100-500 rpm, and the ball milling time is more than 1 h.

3. A ZTA composite ceramic with a high zero stress temperature point, characterized in that: It is prepared by the method according to claim 1 or 2.

4. The ZTA composite ceramic according to claim 3, characterized in that: The thickness ratio of the substrate to the coating of the ZTA composite ceramic is greater than 10.

Citation Information

Patent Citations

  • High temperature creep resistant mullite-cordierite product and preparation method thereof

    CN103664153B

  • A high thermal shock stability cordierite-mullite kiln furniture and its preparation method

    CN110028314B

  • Ltigh crystalline structure iolite mullite kiln, kiln refractory product and calcining technology

    CN1785909A

  • Low-shrinkage coating material for forming compressive stress on surface of ceramic body, preparation method thereof and ceramic product

    CN112047757A

  • Kyanite / aluminum oxide prestressed ceramic and preparation method thereof

    CN112390627A